Fixed Points of αη−ξθ-Expansive Mappings: Saurabh Manro, Peyman Salimi - Team, Support (Thai Journal of Mathematics, 2019)
The aim of this paper is to introduce a new class of expansive mappings - αη-ξθ-expansive mappings and establish fixed point theorems for such mappings in a complete metric space. The resultspresented in this paper substantially generalize and extend several comparable results in the existing literature. As an application, we prove new fixed point results for graphic weak ξθ-expansive mappings.